(untitled) (Raparin Journal of Humanities (RJH), 2024)
The importance of the study is to crystallize the concept of organizational conflict management by developing an organization conflict management scale for the first-division club players in the Kurdistan Region who face conflict through the game and matches. In addition, the players of the first-division clubs under study may benefit from this study in developing their level and getting rid of the difficulties of negative competition, and thus ascending and raising their performance and achieving the best results which helps them increase scientific knowledge of organizational conflict management in matches and its effects and how to confront and address it in a positive way. This study aims to develop an organizational conflict management scale for the first-division club players in the Kurdistan Region, using the descriptive approach in the survey method for its suitability with the nature of the study. Eighteen clubs from the first- division league of Kurdistan Region- Iraq season (2021-2022) were selected as a community of the study. The building sample (292) players were selected in a simple random way (draw) from the basic research sample. The sample of the exploratory experiment was chosen (27) players from Koya sports Club using the intentional method. Mean (M), standard deviation (SD), percentage (%), simple correlation and Spearman’s correlation coefficient were used as a statistical analysis by using (SPSS). Attaining the organizational conflict management scale that the researcher developed through the scientific procedures followed in building the standards, The number of paragraphs of the scale was (46) paragraphs and the distribution of paragraphs on (4) areas.